Behavioral and neurochemical characterization of maternal care effects on juvenile Sprague–Dawley rats - Masís Calvo, Marianella (2013)
Maternal care represents a major constituent of early life environment and has the potential to modulate critical neurobehavioral responses to stress. The aim of the present study was to determine the effects of naturally occurring variations in maternal care on behavioral and neurochemical responses of juvenile Sprague–Dawley rats. A group of dams were classified based on their licking behavior in high and low licking-grooming mothers. Afterwards, the male offspring was tested in a series of behavioral tests: open field test (OFT), elevated plus maze (EPM) and forced swimming test (FST). Additionally, monoamine concentrations were determined postmortem in three brain regions: hippocampus, ventral striatum and prefrontal cortex. Our findings suggest that maternal care variations have an effect on several anxiety-related behaviors in OFT and EPM but not in depression-like behaviors in FST. Such behavioral differences could be related to an increased DOPAC concentration and 5-HT turnover in prefrontal cortex. These evidences suggest that natural variations in maternal care modified some behavioral and neurochemical parameters related with anxiety and stress in this strain